Saint Hildegard of Bingen: A wise woman - Graña Cid, María del Mar (Razón y fe, 2018)
Saint Hildegard of Bingen (1098-1179) was almost unknown before her doctorate. With it, she has not only been rehabilitated eight centuries after her death, but also proposed as a model to both Christian and non-Christian women.
Keywords: Hildegard of Bingen; visionary; mystical; Scivias; Physica; medicine